An appreciative inquiry of facilitative factors within an Early Years setting that promote the development of wellbeing in children - Antczak, Clare Ann (2020)
Working to promote the wellbeing of children is currently a key area of development for the UK government (DoH and DfE, 2017). Whilst the views of teachers of primary and secondary aged children are documented in relation to children’s wellbeing, this remains an under-researched area for Early Years (EY) Practitioners (Bertagno, 2016). Emphasis on promoting wellbeing in young children is beginning to grow with the first statistics for ‘mental disorders’ for preschool children being published in 2018 (NHS Digital, 2018). This research presents an Appreciative Inquiry (AI) exploring the facilitative factors a single EY setting use to promote children’s wellbeing as viewed by EY practitioners and parents. AI is an approach for organisational renewal, originally developed by Cooperrider and Srivastva (1987). The research took place in a Foundation Stage unit of a school with a cross-section of six EY practitioners who work in the setting and four parents who have children attending the setting. A process evaluation (Bushe and Kassam, 2005) was used to evaluate if the AI had been transformative in the educational setting. Participants’ reflections about the AI process were also formally explored to aid this. Thematic Analysis (TA) (Braun and Clarke 2006) detailed two overarching themes that are facilitative factors within the EY setting. These being Relationships and Structures and Systems. TA also detailed two additional overarching themes from EY practitioners’, these being Team Identity and Child-centred. The AI process appeared transformative in the educational setting according to the process evaluation criteria outlined by Bushe and Kassam (2005). Reflections from both groups highlighted the transformative nature of AI and also implications around the positivity principle of AI. Implications for professional EP practice along with implications for EY practitioners are discussed in relation to further promoting young children’s wellbeing.